SEARCH FOR THE COMPOUNDS WHICH PROLONG EFFICIENT REFRACTORY PERIOD AMONG AMINOBENZOTHIAZOLES DERIVATIVES - T. A. Mukhtarov; V. V. Gurova; N. A. Gurova (Фармация и фармакология (Пятигорск), 2015)
The article reviews the experimental research in vitro on a revelation of effective refractory period prolongation properties in aminobenzothiazoles derivatives for isolated atrium of rats. We have provided the comparative characteristics of these compounds in relation with amiodarone.